Produce from Africa’s Gardens: Potential for Leafy Vegetable and Fruit Fermentations - Oguntoyinbo, Folarin A.; Fusco, Vincenzina; Cho, Gyu-Sung; Kabisch, Jan; Neve, Horst; Bockelmann, Wilhelm; Huch, Melanie; Frommherz, Lara; Trierweiler, Bernhard; Becker, Biserka; Benomar, Nabil; Gálvez, Antonio; et al. (Frontiers in Microbiology, 2016)
A rich variety of indigenous fruits and vegetables grow in Africa, which contribute to the nutrition and health of Africa’s populations. Fruits and vegetables have high moisture and are thus inherently prone to accelerated spoilage. Food fermentation still plays a major role in combating food spoilage and foodborne diseases that are prevalent in many of Africa’s resource disadvantaged regions. Lactic acid fermentation is probably the oldest and best-accepted food processing method among the African people, and is largely a home-based process. Fermentation of leafy vegetables and fruits is, however, underutilized in Africa, although such fermented products could contribute towards improving nutrition and food security in this continent, where many are still malnourished and suffer from hidden hunger. Fermentation of leafy vegetables and fruits may not only improve safety and prolong shelf life, but may also enhance the availability of some trace minerals, vitamins and anti-oxidants. Cassava, cow-peas, amaranth, African nightshade and spider plant leaves have a potential for fermentation, as do various fruits for the production of vinegars or fruit beers and wines. What is needed to accelerate efforts for production of fermented leaves and vegetables is the development of fermentation protocols, training of personnel and scale-up of production methods. Furthermore, suitable starter cultures need to be developed and produced to guarantee the success of the fermentations.